Augustine and the Functions of Concupiscence. - Nisula, Timo. (Leiden : BRILL, 2012)
In Augustine and the Functions of Concupiscence, Timo Nisula offers a comprehensive analysis of Augustine's developing views of sinful desire. The book demonstrates how and why concupiscence became such a pregnant concept in Augustine's theology and philosophy.
1. Augustine2. Other Sources; 3. Translations; Studies; Index of Modern Authors; Index of Subjects and Names; Index of Ancient Sources.
Print version record.
Includes bibliographical references and indexes.
Master record variable field(s) change: 072
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430; Lust -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Sex -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Emotions -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; RELIGION -- Christian Theology -- Ethics; RELIGION -- Christian Theology -- Anthropology; 30-600; Electronic books